2020
DOI: 10.4103/eus.eus_10_20
|View full text |Cite
|
Sign up to set email alerts
|

Primary EUS-guided biliary drainage versus ERCP drainage for the management of malignant biliary obstruction: A systematic review and meta-analysis

Abstract: EUS-guided biliary drainage (EUS-BD) has been used as a salvage modality for relief of malignant biliary obstruction (MBO) after a failed ERCP. Multiple recent randomized controlled trials (RCTs) and observational studies have been published to assess the suitability of EUS-BD as a first-line modality for achieving palliative BD. We aimed to perform a systematic review and meta-analysis comparing primary EUS-BD versus ERCP for MBO. We searched PubMed, Medline, and Embase up to January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…In a systematic review and meta-analysis of five studies, 361 patients (190 in the ERCP group and 171 in the EUS group), it was found that the technical and clinical success were comparable. 40 The overall adverse events were similar between the two groups. In the ERCP group, 9.5% of patients developed procedure-related pancreatitis while no patient developed pancreatitis in the EUS group (risk difference ¼ 0.08%, p ¼ 0.02).…”
Section: Recommendationmentioning
confidence: 77%
“…In a systematic review and meta-analysis of five studies, 361 patients (190 in the ERCP group and 171 in the EUS group), it was found that the technical and clinical success were comparable. 40 The overall adverse events were similar between the two groups. In the ERCP group, 9.5% of patients developed procedure-related pancreatitis while no patient developed pancreatitis in the EUS group (risk difference ¼ 0.08%, p ¼ 0.02).…”
Section: Recommendationmentioning
confidence: 77%
“…Os autores concluíram que não existem evidências claras que sustentem a recomendação de preferência por uma das técnicas ou por um dos tipos de próteses. Em 2019 e 2020, foram publicadas três metanálises [33][34][35] que endossam que a DBE possui desempenho semelhante a CPER na desobstrução maligna da via biliar, com alívio da icterícia e oferecendo ainda a vantagem de risco nulo de pancreatite pós procedimento.…”
Section: Coledocoduodenostomia Ecoguiada Versus Hepatogastrostomia Ec...unclassified
“…EUS-BD with transluminal stenting, including EUS-guided hepaticogastrostomy (EUS-HGS), choledochoduodenostomy (EUS-CDS), and antegrade biliary stenting (EUS-ABS), is recommended, especially in patients with malignant biliary obstructions; its effectiveness may be comparable with that of ERCP as the first-line management of certain biliary obstructions [ 7 , 8 , 9 , 10 , 11 ]. Since its first description in 2001 [ 12 ], the procedure has improved and shown high technical and clinical success rates of approximately 95% and 92–94%, respectively [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%